2008
DOI: 10.1111/j.1365-294x.2008.03838.x
|View full text |Cite
|
Sign up to set email alerts
|

Early season herbivore differentially affects plant defence responses to subsequently colonizing herbivores and their abundance in the field

Abstract: Induction of plant defences by early season herbivores can mediate interspecific herbivore competition. We have investigated plant-mediated competition between three herbivorous insects through studies at different levels of biological integration. We have addressed (i) gene expression; (ii) insect behaviour and performance under laboratory conditions; and (iii) population dynamics under field conditions. We studied the expression of genes encoding a trypsin inhibitor and genes that are involved in glucosinola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
274
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(303 citation statements)
references
References 76 publications
8
274
3
1
Order By: Relevance
“…In this perspective, Brassica provides a good study system as several of its defenses have been deeply investigated in different species within the family. Moreover, higher trophic level interactions and the herbivore communities associated with Brassica species have been charted out very well (Gols et al 2008b;Poelman et al 2008;Ahuja et al 2010;Kugimiya et al 2010). With such a global model system it may be more likely to gain a much deeper understanding of interactions between plants (as a whole organism) and their BG-AG insect communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, Brassica provides a good study system as several of its defenses have been deeply investigated in different species within the family. Moreover, higher trophic level interactions and the herbivore communities associated with Brassica species have been charted out very well (Gols et al 2008b;Poelman et al 2008;Ahuja et al 2010;Kugimiya et al 2010). With such a global model system it may be more likely to gain a much deeper understanding of interactions between plants (as a whole organism) and their BG-AG insect communities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, plant defenses induced in response to one attacker may affect plant defenses against another attacker that feeds sequentially or simultaneously on distal parts of the same plant (Karban and Baldwin 1997;Soler et al 2007;Vos et al 2013). In nature, attack by a single herbivore species is unusual and inducible defenses against multiple attackers have been extensively studied (Rodriguez-Saona et al 2005;Poelman et al 2008;Ali and Agrawal 2014). Although most of these studies were constrained to aboveground herbivores, plant-mediated interactions occur also between belowground (BG) and aboveground (AG) herbivores (Hol et al 2004;Bezemer and van Dam 2005;van Dam et al 2005;Soler et al 2007;Erb et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, damage caused by one herbivore species may induce plant chemical defences which in turn influence attack by another herbivore guild [43] as well as arthropod community structure [44]. Such effects are particularly common in systems where early-season herbivores triggers plant induced responses that affect late-season herbivores [45,46]. Surprisingly, however, this area of research has developed independently of plant diversity studies, despite the fact that diversity effects on herbivory would be expected to influence plant induced responses and thus potentially lead to plant-mediated interactions among herbivores.…”
Section: Effects Of Plant Diversity On Plant-insect Herbivore and Hermentioning
confidence: 99%
“…In a field study with Brassica oleracea plants, it was demonstrated that early season herbivory significantly affected plant defense responses to secondary herbivores and the development of their populations (Poelman et al, 2008). Gene expression analyses implicated a dominant role for plant hormones in the regulation of this process.…”
Section: Multispecies Interactions: Juggling the Good The Bad And Tmentioning
confidence: 99%